2020
DOI: 10.1101/2020.05.04.20090977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative proteomics of coeliac gut during 14-day gluten challenge: low-level baseline inflammation despite clinical and histological normality predicts subsequent response

Abstract: Objective To shed light on gut mucosa processes provoked by gluten exposure in coeliac disease, we performed a quantitative proteomic analysis of duodenal tissue from well-treated coeliac patients before and after gluten challenge. Design We extracted and digested proteins from formalin-fixed paraffin-embedded tissue of 19 coeliac disease patients who had been challenged orally with gluten for 14 days. Protein identification and quantification was done by label-free quantitative mass spectrometry-based prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…New observations have been obtained and published challenging gluten in vivo in GFD-CD patients by analyzing before and after gluten introduction on several different pathways such as proliferation, inflammation and differentiation at the intestinal level [25][26][27]. Dotsenko et al, demonstrated that the intestinal morphology in patients on a strict GFD was similar to that measured in control subjects [25].…”
Section: Gfd-cd Patients Before and After Gluten Challenge In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…New observations have been obtained and published challenging gluten in vivo in GFD-CD patients by analyzing before and after gluten introduction on several different pathways such as proliferation, inflammation and differentiation at the intestinal level [25][26][27]. Dotsenko et al, demonstrated that the intestinal morphology in patients on a strict GFD was similar to that measured in control subjects [25].…”
Section: Gfd-cd Patients Before and After Gluten Challenge In Vivomentioning
confidence: 99%
“…Another recent paper by Stamnaes J. et al [26,27] shows by proteomics analysis that before being challenged in GFD-CD patients, epithelial inflammation is already in the intestines, with changes indicative of minor crypt hyperplasia and low-grade inflammation in the serum. After challenge with gluten, an increase in the same proteins, already altered at base line in GFD-CD responders, was found.…”
Section: Gfd-cd Patients Before and After Gluten Challenge In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Gliadin and the undigested gliadin peptide p. 31–43 have also been shown to be able to induce inflammation in CD. In particular this peptide and the peptic tryptic product of gliadin can induce NFkB and the other markers of inflammation in vitro and in vivo [ 25 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Constitutive alterations of CD cells, in the absence of a gliadin challenge, have been described in different systems and both in vivo and in vitro assays [ 35 , 36 , 37 , 38 ]. These alterations point to a derangement of signaling, proliferation and the cytoskeleton, leading to inflammation, innate immunity activation and cellular stress in the enterocytes and fibroblasts of CD patients.…”
Section: Discussionmentioning
confidence: 99%